Estado cosmopolita en América Latina (2018)
The present article focuses on reflecting on the conception of the cosmopolitan Government model in Latin America, starting with the idea of what has been called traditional cosmopolitanism for the purposes of research, sustained by Kant (1795), as opposed to the modern proposal of cosmopolitanism sustained by other authors such as Cortina, 1997; Nussbaum, 1999; de Sousa Santos, 2010, this with the purpose of delimiting the concept. Afterwards it emphasizes in the failure of the models of Government currently prevailing in most Latin American countries, and how the cosmopolitan Government represents a solution for what these models have failed to achieve; the same applies to those legal theories and other branches that support the viability of the cosmopolitan Government model.